Performance Evaluation of Bentonite–Nano SiO₂ as an Adsorbent in the Decolorization Process of Rhodamine B - Regna Tri Jayanti; Miftahul Khairati; Enny Nurmalasari; Puji Rahayu; Dennis Farina Nury; Okti Ulandari; Andhini Putri Trianita (Jurnal Ilmiah Berkala Sains dan Terapan Kimia, 2026)
Among various sources of industrial water pollution, effluents from printing, dyeing, and textile processes represent one of the most significant environmental threats. These wastewaters contain numerous toxic and hazardous substances that are difficult to biodegrade. This study investigates the synthesis, characterization, and adsorption performance of a Bentonite–Nano SiO₂ composite for the removal of Rhodamine B dye from aqueous solutions. The research was conducted in two main stages: the preparation of the Bentonite–Nano SiO₂ composite and the evaluation of its adsorption performance at various adsorbent concentrations and contact times. The composite was synthesized by dispersing nano-silica (15% w/w) into bentonite using ethanol as the solvent, followed by stirring, filtration, and drying processes. Characterization using Scanning Electron Microscopy (SEM) and Fourier Transform Infrared Spectroscopy (FTIR) confirmed successful modification. Adsorption tests showed that Rhodamine B removal efficiency increased with higher adsorbent concentration, reaching optimal conditions at 0.75% (w/v) with a removal efficiency of 90.2% after a contact time of 10–15 minutes. The enhanced adsorption performance was attributed to the larger surface area, higher porosity, and increased number of active sites resulting from the incorporation of nano-silica